Book Review: Laurenţiu Vlad, „Istorii româneşti ale ideii de “Europa”, secolele XVII-XXI (imagini, note, reflecţii)”, Iaşi, Institutul European, 2021, 340 p. - MITU, Sorin (Studia Universitatis Babeș-Bolyai Historia, 2021)
Europe, and Romanian stances on the European paradigm seem to no longer represent today’s topics of keen interest for Romanian readers with a penchant for history, unlike in the 1990s, when collections such as “The Construction of Europe” or “The Third Europe” were published by Polirom, and when authors such as Alexandru Duţu, Adrian Marino or Victor Neumann wrote about such issues. Notwithstanding all this, Professor Laurenţiu Vlad from the Bucharest University has deliberately ignored this recent trend and, under the auspices of the European Institute, brought back to our attention the Romanian histories of the European idea, convincing us that they deserve to be further explored.